ANALISIS INKLUSI KEUANGAN PADA KOMUNITAS WISATAWAN DOMESTIK - Ekayana Sangkasari Paranita; Endang Wulandari (Universitas Lambung Mangkurat, 2022)
The purpose of this study is analyze the factors that influence the financial inclusion of domestic tourism with a quantitative approach. The research findings contain novelty of empirical research which is expected to contribute to the study of financial inclusion and the study of the preferences of tourism which are still very limited. The object of research is a member of the Cheap Holidays Facebook group who has been actively traveling in the last three years. Based on the multivariate linear regression analysis technique, partially it turns out that only financial behavior variables have a significant positive effect on financial inclusion, while financial literacy and financial skills variables have no significant effect on financial inclusion. However, simultaneously these three variables have a significant positive effect on financial inclusion. It is recommended that further research expands respondents and integrates demographic and geographic data for domestic tourism for a more comprehensive analysis of the determinants of financial inclusion. Keywords: financial literacy, financial skills, financial behavior, financial inclusion.